Mutations in Plasmodium falciparum dihydrofolate reductase and dihydropteroate synthase and epidemiologic patterns of pyrimethamine-sulfadoxine use and resistance - Plowe, C V; Cortese, J F; Djimde, A; Nwanyanwu, O C; Watkins, W M; Winstanley, P A; Estrada-Franco, J G; Mollinedo, R E; Avila, J C; Cespedes, J L; Carter, D; Doumbo, O K (The Journal of infectious diseases, 1997)
To assess the relationship between mutations in Plasmodium falciparum dihydrofolate reductase (DHFR) and dihydropteroate synthase (DHPS) and clinical pyrimethamine-sulfadoxine resistance, polymerase chain reaction surveys and analyses for new mutations were conducted in four countries with increasing levels of pyrimethamine-sulfadoxine resistance: Mali, Kenya, Malawi, and Bolivia. Prevalence of mutations at DHFR codon 108 and a new mutation at DHPS 540 correlated with increased pyrimethamine-sulfadoxine resistance (P < .05). Mutations at DHFR 51, DHFR 59, and DHPS 437 correlated with resistance without achieving statistical significance. Mutations at DHFR 164 and DHPS 581 were common in Bolivia, where pyrimethamine-sulfadoxine resistance is widespread, but absent in African sites. Two new DHFR mutations, a point mutation at codon 50 and an insert at codon 30, were found only in Bolivia. DHFR and DHPS mutations occur in a progressive, stepwise fashion. Identification of specific sets of mutations causing in vivo drug failure may lead to the development of molecular surveillance methods for pyrimethamine-sulfadoxine resistance.